Game Design as an Autonomous Research Subject - Neves, Pedro Pinto; Zagalo, Nelson (Information (Basel), 2021)
This paper examines the methods and systems of game design from the standpoint of existing method proposals failing to establish a common basis for systematizing design knowledge, which this paper aims to help resolve. Game design has often been subsumed by game development and associated disciplines, and game design methodology has often been subsumed by game analysis. This paper reviews related work in defining game design as an autonomous research subject and then divides the methods and systems of game design into complementary methods and core methods, with only the latter, consisting chiefly of design patterns, attempting to systematize how game design knowledge is generated. Seminal game patterns have been descriptive rather than -prescriptive and so have failed to find the requisite practitioner adoption to fulfill their role as a living method. One recent pattern approach has sought to resolve this issue by promoting pattern usage generally over the adoption of a particular language. This paper outlines an alternate and possibly complementary approach of a novel, practical basis for game design literacy for helping core methods work as a basis for systematizing game design knowledge. The proposed basis sacrifices descriptiveness to prescriptiveness to shape methods in that direction.